Teatr na wodzie. Wodny żywioł we współczesnym teatrze polskim - Kostaszuk-Romanowska, Monika (Załącznik Kulturoznawczy, 2023)
In view of theatrical performances, water is not only an important cultural trajectory, but also an attractive, though very special, stage material. The authoress draws attention to the ambivalent character of water as an element of the spectacle. Water identifies the very essence of theatricality, which consists of the constant oscillation between illusion and reality. The effect of real water – limited by technical restrictions and in effect artificial to some extent – has an unquestionable spectacle value. The authoress recalls selected performances whose creators have chosen large-scale solutions and introduced a large amount of water to the stage. In this way, she shows how they create the symbolic value of aqua motives, how they use their semantic and sensual potential in the process of translating the cultural connotations of water into signs and meanings of a particular show.